Jejunum ileal intestinal atresia. - Claudio J. Puente Fonseca (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
The intestinal atresia is one of the most important causes of intestinal obstruction in newborn. They constitute aorund 95% of total intestinal obstructions in this age group. Most of intestinal atresias are jejunoieal atresia. Although it is not frequent their relationship with other congenital anomalies, has been described the association in some cases with defects of intestine rotation, meconium peritonitis, with meconium ileus and rarely with the Hirschsprung diseases. The hereditary character has also been described in certain multiple intestinal atresias. We presented the Good Clinical Practices Guideline for Jejunoileal atresia, approved by consensus in the 1st National Good Clinical Practices Workshop in Pediatric Surgery (Cienfuegos, Cuba, March 7 - 9, 2002).